Daya Terima Puding dengan Substitusi Susu Kedelai dan Penambahan Wortel sebagai Alternatif Makanan Selingan untuk Pencegahan Hipertensi - Madania Ulfa; Asrul Bahar (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2024)
Hypertension is a condition when systolic blood pressure >140 mmHg or diastolic >90 mmHg. Soy milk and carrot pudding is expected to be able to meet the needs of snacks tp prevent the hypertension. The research aims to determine the effect of soy milk substitution, addition of carrots and interaction of the two factors (soy milk substitution and carrot addition) on the acceptability of pudding, also know the fat, potassium, sodium and isoflavone content in the best formula. The research used a pure experimental method with 6 treatments, namely soy milk substitution (70% and 80%) and carrot addition (60%, 70% and 80%), which were tested on 50 untrained panelists. Data were analyzed statistically using the Two Way Anova test and the Duncan test. The results of the research showed that the substitution of soy milk had an effect on the color, flavour and taste of the pudding, the addition of carrots had an effect on the color and taste of the pudding and there was no interaction effect between the two factors on the color, flavor, taste or texture of the pudding. The best pudding product was found in the S2W3 formula (80% soy milk substitution and 80% carrot addition) which contains 1.36% fat, 28.11 mg potassium, 34 mg sodium and 21.8 mg isoflavones per 100 grams of ingredients.